1993
DOI: 10.1136/bmj.307.6912.1111
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of osteoporotic fractures by postural instability and bone density.

Abstract: Objective-To investigate the utility of risk factors such as bone mineral density, lifestyle, and postural stability in the prediction of osteoporotic fractures.Design-Longitudinal, epidemiological, and population based survey.Setting-City ofDubbo, New South Wales. Subjects-All residents of Dubbo aged > 60 on 1 January 1989.Main outcome measure-Incidence of fracture for individual subjects.Results-The overall incidence of atraumatic fractures in men and women was 1.9% and 3.1% per annum respectively. The predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
331
3
11

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 536 publications
(356 citation statements)
references
References 32 publications
5
331
3
11
Order By: Relevance
“…BMD measurements have been shown to predict hip fracture probability in the range 17-43% in a 6-year period [7]. Although the prediction of fractures by simple risk indicators may be not as effective as by BMD measurements, other risk factors, not related to bone, have been shown to supply additional information to BMD in the prediction of hip fractures [4,15,16]. Other easily obtainable risk indicators, not included in this study (e.g.…”
Section: Discussionmentioning
confidence: 94%
“…BMD measurements have been shown to predict hip fracture probability in the range 17-43% in a 6-year period [7]. Although the prediction of fractures by simple risk indicators may be not as effective as by BMD measurements, other risk factors, not related to bone, have been shown to supply additional information to BMD in the prediction of hip fractures [4,15,16]. Other easily obtainable risk indicators, not included in this study (e.g.…”
Section: Discussionmentioning
confidence: 94%
“…(20)(21)(22)(23) Briefly, in 1989, all men and women aged 60 years or above (as of 1989) living in Dubbo, a city of approximately 32,000 people 400 km northwest of Sydney (Australia), were invited to participate in an epidemiologic study. At that time, the population consisted of 1581 men and 2095 women aged 60 years or older, of whom 98.6% were white and 1.4% were indigenous aboriginal.…”
Section: Study Setting and Participantsmentioning
confidence: 99%
“…Fractures occurring during the study period were identified for residents of the Dubbo local government area through radiologists' reports from the two centers providing X-ray services, as described previously. (20,21) Fractures were included only if the report of fracture was definite and, on interview, had occurred with low trauma (eg, fall from standing height or less). Fractures clearly owing to major trauma (eg, motor vehicle accidents), those owing to underlying diseases (eg, cancer or bone-related diseases), or those of digit, skull, or cervical spine were excluded from the analysis.…”
Section: Ascertainment Of Fracturementioning
confidence: 99%
“…(4,(8)(9)(10) Arguments to support the latter focus on reports that men fracture at a higher level of BMD than women. (11)(12)(13) These two sets of observations are often presented as in conflict. (14) A recent review by Khosla and colleagues (15) concluded that the most appropriate definition for osteoporosis in men, in the absence of fractures, was a major unresolved issue and should be the focus of future research.…”
Section: Introductionmentioning
confidence: 99%